2023
DOI: 10.3390/soc13020040
|View full text |Cite
|
Sign up to set email alerts
|

At the Origins of Migration Choices: A Survey of Students at Two South European Universities

Abstract: Migration research has long highlighted the role of factors influencing migration flows at the structural level. Recent literature has shifted researchers’ attention to the individual drivers influencing the definition of migration strategies and, before that, the individual propensity for mobility. In this paper, we present the results of a multiple regression model applied to data collected by means of an online survey of students at the universities of Salerno (Italy) and Extremadura (Spain). The model high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to Sadeghi et al (2023) mobility students possess these same factors -extraversion and openness. Mobility experience as a sign of direct experience of migration has a positive and statistically significant effect on migration propensity (Addeo et al, 2023). A study by Weber and Saarela (2023) also proves that student migrants were the most likely to immigrate for a second time.…”
Section: Students' Mobility Analytics and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to Sadeghi et al (2023) mobility students possess these same factors -extraversion and openness. Mobility experience as a sign of direct experience of migration has a positive and statistically significant effect on migration propensity (Addeo et al, 2023). A study by Weber and Saarela (2023) also proves that student migrants were the most likely to immigrate for a second time.…”
Section: Students' Mobility Analytics and Discussionmentioning
confidence: 92%
“…However, according to Luque-Martínez et al (2023) participants of the exchange programs demonstrated higher willingness to repeat their university studies. Previous research on the reasoning for students returning to their homes after studying at the university, conducted, e.g., for Portugal (Simões et al, 2021), Switzerland (Oggenfuss & Wolter, 2019), Italy, and Spain (Addeo et al, 2023) on the country's internal and international mobility, can be considered for designing a mobility data-management system to track behavioural factors. An ongoing war in Ukraine showed to be also influencing students' return/non-return decisions.…”
Section: Students' Mobility Analytics and Discussionmentioning
confidence: 99%